Ostomy Creation in Neonates with Acute Abdominal Disease: Friend or Foe? - van Zoonen, Anne G. J. F.; Schurink, Maarten; Bos, Arend F.; Heineman, Erik; Hulscher, Jan B. F. (European Journal of Pediatric Surgery, 2012)
Background An ostomy seems a safe alternative in neonates with an acute abdomen when immediate restoration of bowel continuity is deemed undesirable. Faced with several complications in our center, and the feeling we are not the only center with these complications, we decided to assess the rate and type of complications after both ostomy creation and closure.Methods All data regarding neonates (<30 days of age) who underwent a laparotomy for a suspected abdominal emergency in the period 2000 to 2010 were retrospectively analyzed. These data included demographics such as gender, gestational age, and birth weight. Disease etiology was defined and various features of the enterostomy were analyzed. These features included type, location, time to ostomy take down, and complications and mortality directly related to both creation and closure of the ostomy.Results A total of 155 patients who underwent a laparotomy for suspect acute abdomen were identified. Median gestational age was 33 weeks (range 25 to 40) and median birth weight was 1926 g (range 560 to 4380). Median age at laparotomy was 8 days (range 0 to 30). Indications for surgery were necrotizing enterocolitis (n = 38), spontaneous intestinal perforation (n = 11), intestinal atresia (n = 9) or obstruction (n = 5), and volvulus (n = 4). An ostomy was created in 67 patients (67/155: 43%): 38 boys and 29 girls. There were 8 jejuno-, 49 ileo-, and 10 colostomies created. In almost all cases (94%), a mucous fistula was also constructed.In 23 patients (23/67: 34%) ostomy-related complications occurred. Most frequent were high output ostomy (n = 10) and necrosis of the enterostomy (n = 7). Due to either one of the complications, nine patients (9/67: 13%) needed a reoperation.In this study, 11 patients died before ostomy closure could occur. In 53 patients, the ostomy was closed after a median of 107 days (range 4 to 299).After ostomy closure, complications occurred in 13 cases (13/53: 25%). Seven patients (7/53: 13%) needed another reoperation because of anastomotic leakage (n = 4), adhesions (n = 2), or incisional hernia (n = 1). There was no closure-related mortality.Conclusion Although creating a temporary ostomy in newborns is preferable in certain situations, there is a considerable occurrence of complications and reoperations.
Keywords: ostomy; neonate; acute abdomen